Calculation of the goffered multilayered composite cylindrical shells - Bich, Dao Huy; Bay, Vu Khac; Dung, Dao Van; Thinh, Tran Ich; Vinh, Pham Chi (Vietnam Journal of Mechanics, 1997)
By using the effective modulus theory and Seydel assumptions the governing equations of the goffered multilayered composite cylindrical shell are formulated. Solution to the problem 1n term of displacements is given by the operator method, while the solution in term of stress function and deflection is obtained by Bubnov-Galerkin method in choosing appropriate forms of these quantities.